(untitled) (Research, Society and Development, 2022)
The aim of this research was to describe the benefits of exergames as a tool to promote physical activity in children. This is an integrative review of articles published in Lilacs, SciELO and PubMed databases, from 2011 to 2021, selected using exact descriptors and synonyms in Portuguese and English for the terms “exergames”, “physical activity” and “children”. Articles with full text available online were included; for free; in Portuguese, English or Spanish; to answer the guiding question and; dealt with experimental studies or literature reviews that sought to analyze exergames as a physical activity tool in children (up to 11 years). The final sample consisted of eight articles. All studies found that the increase in the level of physical activity was the main benefit of the practice of exergames, in addition to increasing motivation, energy expenditure, heart rate, improving body composition, anthropometric measures and health in general, especially in games that involve the practice of sports (Wii Sports), dancing (Dance Dance Revolution and Just Dance) and physical exercises (Wii Fit). Exergames are an effective tool in promoting physical activity in children. However, it is important that they be used in a way that complements conventional physical activities, so that you can have a better use of all their benefits and encourage healthier lifestyle habits.